(untitled) (Damascus University Journal for legal sciences, 2025)
The extent of the damage to the owner caused by the seizure of his aircraft in reserve by creditors is no secret, in order to guarantee their rights, and that damage is mainly the result of the seriousness of the effects of the pretrial detention, as these effects are directly directed towards obstructing the commercial exploitation of the aircraft in order to prevent its use and to restrict its investment during the period of detention. The content of these effects must be examined in order to overcome them and to provide legal protection to those affected, as this has negative consequences for international air transport services as a whole.